2020
DOI: 10.1021/acs.jpcc.0c08831
|View full text |Cite
|
Sign up to set email alerts
|

Anions as Intermediates in Plasmon Enhanced Photocatalytic Reactions

Abstract: Hot electron transfer to unoccupied molecular orbitals is the most popularized mechanism for plasmon enhanced photocatalytic reactions, while a few reactions have been attributed to near-field enhanced intramolecular adsorbate electronic photoexcitation. In this Perspective, it is argued that the role of hot electrons may be limited to preparing anionic complexes that can undergo further chemical transformation via photoexcitation to dissociative potential energy surfaces. The proposed mechanism is based on ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 104 publications
1
4
0
Order By: Relevance
“…The terminal N2 initially picks up more negative charge than N1. This charge transfer profile provides support for the idea that transient negative ions play an important role in plasmon-mediated molecular activations . For this system (parallel adsorbate, longitudinal plasmon excitation, 0.03 a.u.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The terminal N2 initially picks up more negative charge than N1. This charge transfer profile provides support for the idea that transient negative ions play an important role in plasmon-mediated molecular activations . For this system (parallel adsorbate, longitudinal plasmon excitation, 0.03 a.u.…”
Section: Resultssupporting
confidence: 67%
“…This charge transfer profile provides support for the idea that transient negative ions play an important role in plasmon-mediated molecular activations. 55 For this system (parallel adsorbate, longitudinal plasmon excitation, 0.03 a.u. field strength), a transient negative ion forms within the first 5 fs of the simulation, then dissipates around 42 fs into the simulation.…”
Section: Resultsmentioning
confidence: 99%
“…The *CO 2 to *CO pathway has been studied extensively, and various stabilization mechanisms have been proposed, for example, some works have shown that the *CO 2 – is stabilized by a single proton transfer from water and then, through a proton-electron transfer, reduced to *CO. , Another pathway proposed by Sheng and collaborators is that the *CO 2 – is reduced to *CO through a single electron transfer of a *CO 2 dimer radical anion to convert it to *CO and CO 3 2– . Other works indicate that the pathway from CO 2 toward the intermediate *CO strongly depends on the excitation wavelength and the nature of the catalyst, where recent research suggests that the activation and division of the CO 2 molecule depends on hot electrons produced from the decay of and that the strong reduction of this molecule from these hot electrons is accompanied by its stabilization through the surface (S) and solvent molecules (Ln) as shown in the following equation: false( normalS * CO 2 false) Ln + h v false( normalS false* normalO false) Ln * CO where the *CO 2 – dissociation takes place on the excited state potential energy surface, which may yield an adsorbed *CO molecule. The formation of adsorbed *CO agrees with our in situ time-resolved experiments, where we observe a rapid increase in *CO during the first minutes of electrolysis that then persists during the entire time the experiment is carried out.…”
Section: Mechanism and Discussionmentioning
confidence: 99%
“…It has been well demonstrated field-enhanced direct excitation of adsorbate or adsorbate-metal complex plays a critical role in plasmon induced chemical reactions. 29,30 An in situ monitoring of FA dehydrogenation by a single-particle spectroscopy also indicated FA molecules could be activated through direct energy transfer or indirect energy transfer over Au−Ag@Pd or Au@Pd nanorods, 13 and the strong EF at the tips of the nanorods particularly contributed to FA adsorption and activation. 11 It is thus believed that the distinct near-field enhancement of the PDA@AgPd-400 greatly contributes to its highest R plas .…”
Section: ■ Results and Discussionmentioning
confidence: 99%